Optimal LEACH protocol with modified bat algorithm for big data sensing systems in Internet of Things - Cui, Zhihua; Cao, Yang; Cai, Xingjuan; Cai, Jianghui; Chen, Jinjun (Journal of parallel and distributed computing, 2019)
Big data sensing system (BDSS) plays an important role in the Internet of Things, in which how to reduce power consumption is one crucial problem. Currently, low energy adaptive clustering hierarchy (LEACH) protocol is one well-known algorithm used in BDSS with low energy cost. In this paper, a new variant of bat algorithm combined with centroid strategy is introduced. Three different centroid strategies with six different designs are introduced. In addition, the velocity inertia-free update equation is also provided. The optimization performance is verified by CEC2013 benchmarks in those designs against standard BA. Simulation results prove that the bat algorithm with weighted harmonic centroid (WHCBA) strategy is superior to other algorithms. By integrating WHCBA into LEACH protocol, we develop a two-stage cluster-head node selection strategy and can save more energy compared to the standard LEACH protocol. •Modified bat algorithm with centroid strategy is designed.•Six different centroid strategies are designed and compared.•Velocity inertia-free update equation is designed.•Bat algorithm with weighted harmonic centroid strategy is used to optimize the performance of LEACH protocol, and compared with other four algorithms.